2001
DOI: 10.1152/ajpregu.2001.281.5.r1474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic cardiac decentralization on functional properties of canine intracardiac neurons in vitro

Abstract: Although intrinsic cardiac neurons display ongoing activity after chronic interruption of extrinsic autonomic inputs to the heart, the effects of decentralization on individual neurons remain unknown. The objective of this study was to determine the effects of chronic (3-4 wk) surgical decentralization on intracellular properties of, and neurotransmission among, neurons contained within the canine intrinsic right atrial ganglionated plexus in vitro. Properties of neurons from decentralized hearts were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Low-level vagal nerve stimulation markedly attenuated the hyperactive state of the GP, thereby suppressing AF. In a recent experimental study, we recorded the neural activity of the GP and found that several hours of induced AF caused a significant increase in the amplitude and frequency, whereas low level vagal nerve stimulation not only suppressed AF propensity but also the increased amplitude and frequency of the hyperactive GP [92]. A recent clinical report from our group has confirmed that low-level vagal nerve stimulation can mitigate AF in patients with the paroxysmal form of this arrhythmia [88].…”
Section: Additional Supporting Studiesmentioning
confidence: 85%
See 2 more Smart Citations
“…Low-level vagal nerve stimulation markedly attenuated the hyperactive state of the GP, thereby suppressing AF. In a recent experimental study, we recorded the neural activity of the GP and found that several hours of induced AF caused a significant increase in the amplitude and frequency, whereas low level vagal nerve stimulation not only suppressed AF propensity but also the increased amplitude and frequency of the hyperactive GP [92]. A recent clinical report from our group has confirmed that low-level vagal nerve stimulation can mitigate AF in patients with the paroxysmal form of this arrhythmia [88].…”
Section: Additional Supporting Studiesmentioning
confidence: 85%
“…Subsequently, a series of experimental studies have been published [87][88][89][90][91] in which we used low-level vagosympathetic trunk electrical stimulation at levels 10% and 50% which did not slow the heart rate or slow atrio ventricular conduction (AVC). In an experimental model of induced AF, we found that the nerve clusters called ganglionated plexi (GP) found in specific vulnerable sites in the atria became hyperactive under the influence of excessive release of cholinergic (parasympathetic) and adrenergic (sympathetic) neurotransmitters [92]. In this regard, Smith et al [92] tested the function of the GP, weeks after separation of the vagal and sympathetic nerves from the aforementioned structures.…”
Section: Additional Supporting Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an experimental model of induced AF, it was found that the nerve clusters called ganglionated plexi (GP) found in specific vulnerable sites in the atria became hyperactive under the influence of excessive release of cholinergic (parasympathetic) and adrenergic (sympathetic) neurotransmitters. In this regard, Smith et al [85] tested the function of the GP, weeks after separation of the vagal and sympathetic nerves from the aforementioned structures. Not only did the intrinsic GP neurons remain viable but their responsiveness was enhanced.…”
Section: Review Of Experimental Studiesmentioning
confidence: 99%
“…Acetylcholine (Ach) released by vagal nerve may cause hyperpolarization and a bradycardia by activating a subset of muscarinic receptors . As the sinus venosus possesses plenty of adrenergic and muscarinic receptors, the influence of vagal input on pacemaking activity could be observed much distinctively . In recent years, high frequency (HF) and low frequency (LF) spectra of the HRV have been employed to study the dynamic regulation of pacemaking activity …”
Section: Introductionmentioning
confidence: 99%